Brand Experience as a Mediating Mechanism Between CSR Initiatives, CSR Supportive Behaviour, and Consumer Brand Loyalty - Zhu, Teng; Jamal , Jamilah; Muda, Suhaini (International Review of Management and Marketing, 2026)
This study aims to examine the relationship between CSR initiatives (CSRI), CSR-supportive behaviours (CSRSB), brand experience (BE), and consumer brand loyalty (CBL), with brand experience as a mediating variable in four major cities of China. A total of 550 respondents has been surveyed and this paper employed structural equation modeling (SEM) for data analysis. The results indicate that CSRI positively influences both CSRSB and BE. Additionally, both BE and CBL are significantly impacted by CSRSB. The mediation analysis confirms that BE partially mediates the relationship between CSRI and CBL in the present study. This indicates that the important role of brand experience in consumer loyalty. While CSR efforts contribute to consumer commitment, a positive brand experience further strengthens this relationship. The findings provide strategic insights for brand managers, recommending enhanced consumer-brand interactions to maximize the impact of CSR.